O ego como problema existencial em Sartre - Machado, Fabiane Schneider (2012)
The work presents the thesis of Sartre about the Ego, namely, it is a transcendent object to consciousness and, hence, is situated in the existential dominion. It was looked for demonstrating that this thesis was engendered from the defense of intentional consciousness and the distinction between the irreflective and the reflexive consciousness. The purpose that comes after this is to make clear the distance taken by Sartre from proposals found to the Ego in the philosophical tradition, more specifically, from proposals of Descartes, Kant and Husserl. After that, it is made explicit how the Ego constitution is done, while a transcendent pole of other transcendent units, namely: the states, the actions and the qualities. Finally, the consequences to the transcendental and existential spheres of affirmation that impose the transcendent character to the Ego are investigated. It is presented as results: I. the evidence of the distance from the Sartre s comprehension of epoché in relation to the one by Husserl; II. the understanding of Ego as an object that urgently, is characterized by dubiety and irrationality; III. the conclusion that there is a change in the treatment about the personhood of consciousness between the works The Transcendence of the Ego and Being and Nothingness; and IV. the connection between the emptying of consciousness and the possibility of moral action. The first result is due to the fact that the epoché will not be considered a procedure, just as in Husserl, but as a torment that is imposed by the spontaneity which marks the Sartre s definition of consciousness, in that there is no transcendental Ego. The second, records that any intuition of the Ego can be contradicted by a new intuition and also, its irrational character is what allows to say that, despite of being an object, it is given as a producer of states and actions. The third, illustrates that the changes between the listed works is attributed to an approximation between the irreflected and reflexive consciousness done in Being and Nothingness, which equalize the consciousness of the Ego to a transcendental field without subject. The last result inscribes the necessity of abandonment of any sedimented sense, as well as of any previous human essential to its existence, to allow affirm the freedom as the insignia of men.